Asperger's children the origins of autism in Nazi Vienna - Sheffer, Edith (W.W. Norton & Company, 2018)
Chapter 1. Enter the experts -- Chapter 2. The clinic's diagnosis -- Chapter 3. Nazi psychiatry & social spirit -- Chapter 4. Indexing lives -- Chapter 5. Fatal theories -- Chapter 6. Asperger & the killing system -- Chapter 7. Girls & boys -- Chapter 8. The daily life of death -- Chapter 9. In service to the volk -- Chapter 10. Reckoning
Includes bibliographical references and index
Keywords: Asperger, Hans; Asperger, Hans -- 1906-1980; Erziehungsheim Am Spiegelgrund; Geschichte 1939-1945; Asperger's syndrome in children -- Patients -- Austria -- Vienna -- History; Asperger's syndrome in children -- Diagnosis -- Austria -- Vienna -- 20th century; Asperger's syndrome in children -- Austria -- Vienna -- History -- 1930-1940; Jugendpsychiatrie; Kindestötung; Euthanasie -- Nationalsozialismus; Nationalsozialistisches Verbrechen; Kind; Jugend; Asperger-Syndrom; Autismus; Kinderpsychiatrie; Wien